DOES SPIRIT OF NATIONALISM STILL EXIST THROUGH GUIDANCE & COUNSELING SERVICE ? (The Fieldtrip Study Analysis at (SIKL) Indonesian School Students of Kuala Lumpur) - Nisa’, Siti Liana Nurun; Azmi, Khilman Rofi' (IAIN Kudus, 2021)
Does Spirit Of Nationalism Still Exist Through Guidance & Counseling Service? (The Fieldtrip Study Analysis at (SIKL) Indonesian School Students of Kuala Lumpur). This study aims to describe the spirit of nationalism in guidance and counseling services (analytical studies at the Indonesian School of Kuala Lumpur (SIKL). This research uses a field visit study method. Where field study visits are conducted online via zoom. The approach used is qualitative. This approach is descriptive based on observations in the form of words or observed behavior. The data sources are diverse, such as observation notes, history, and interview notes. While this article is the source of the data from interviews. The research data collected was then analyzed using a descriptive analysis approach. The results of the study indicate that BK teachers have an important role in helping the success of character education. In Malaysia, there are many Indonesians living there. So, the Kuala Lumpur Indonesian School is presented as an effort for the Indonesian people to instill in every citizen everywhere to be able to experience an integrated education, namely the national education system. SIKL is an overseas Indonesian school that is committed to educating students and promoting Indonesian culture in the global community. There are several forms of activities that support the character of nationalism, namely by holding extracurricular arts, expression stages, scouts, and cultural diplomacy. From these activities, SIKL students became students with strong nationalist characters and became agents of promoters of Indonesian culture in Malaysia.Keywords: Guidance and Counseling; Spirit Nationalism; Kuala Lumpur Indonesian School Students